Prevalence and Genetic Analysis of Thalassemia and Hemoglobinopathy in Different Ethnic Groups and Regions in Hainan Island, Southeast China - Wang, Min; Zhang, Xiaozhuang; Zhang, Yubin; Xiao, Meifang (Frontiers in Genetics, 2022)
Background There are limited studies on the molecular profile of thalassemia in Hainan, the free trade island in China. Our aim was to reveal the prevalence and molecular mutation spectrum of thalassemia in different ethnic groups and regions of Hainan through a large sample study for the first time. Methods A total of 231,596 individuals from 19 cities and counties in Hainan were screened by hematological parameters analysis, and further genetic analysis were performed on individuals with MCV less than 82fL. Results Totally, 31780 (13.72%) subjects were diagnosed as thalassemia carriers. The overall prevalence of α-thalassemia, β-thalassemia and α+β-thalassemia were 11.04%, 1.48% and 1.20% respectively. We further analyzed the molecular profiles of thalassemia in various ethnic groups, and mainly compared the difference between Han and Li. The results showed that the frequency of thalassemia in Li population (47.03%) was much higher than that in Han (9.37%). Except for β-thalassemia (1.31% of Li vs.1.47% of Han), the frequency of α-thalassemia (39.59% of Li vs.7.35% of Han) and α+β-thalassemia (6.13% of Li vs.0.56% of Han) in Li were obviously higher than those in Han. The high-frequent genotypes of α-thalassemia in Han were αα/--SEA (25.55%), -α3.7/αα (22.17%), -α4.2/αα (21.59%), αWSα/αα (8.93%), -α3.7/-α4.2 (4.17%), and those of Li were -α4.2/αα (17.24%), -α3.7/αα (17.16%), -α3.7/-α4.2 (15.09%), αWSα/αα (9.69%), αWSα/-α3.7 (8.06%) respectively. The αα/--SEA was the highest genotype of α-thalassemia in Han, but only accounting for 1.87% in Li. For β-thalassemia, the top three high-frequent genotypes in both Han and Li were βCD41/42(-TTCT)/βN, β-28(A＞G)/βN, βIVS-Ⅱ-654(C＞T)/βN, but the frequency of βCD41/42(-TTCT)/βN in Li (90.96%) was much higher than that in Han (56.32%) and the data reported in other provinces of China. Additionally, the prevalence of thalassemia ranged from 8.16% to 34.35% in Hainan, Wuzhishan, Baoting, Qiongzhong, Baisha have the higher prevalence than other areas. Conclusion Our study revealed the characteristics of ethnic and regional differences in the prevalence of thalassaemia in childbearing age population of Hainan for the first time, indicating that the prevalence of thalassemia among Li nationality is the highest in China. Those findings will be useful for genetic counseling and prevention of thalassemia.